IMPLEMENTATION RATIONAL EMOTIVE BEHAVIOR THERAPY (REBT) APPROACH IN IMPROVING PSYCHOLOGICAL RESILIENCE OF ADOLESCENTS: A Literature Review In Guidance And Counseling Education - Nabila, Fairuz; Setyawan, Aris (Jurnal Asy-Syukriyyah, 2024)
The purpose of this study was to examine in more depth the effectiveness of the REBT approach in improving adolescent resilience through an analysis of relevant literature. The research method used was a literature review by analyzing articles, books, and journals that were relevant to the relationship between the Rational Emotive Behavior Therapy (REBT) approach and resilience skills. Based on the literature review, it was found that REBT is not only effective in improving adolescent resilience, but can also increase self-esteem and reduce anxiety, two factors that are closely related to resilience. Previous studies have shown that by intervening in irrational beliefs, REBT can strengthen adolescents' ability to deal with stress and difficulties, thereby improving their mental well-being.